DIGITAL MINDFUL LEARNING DAN KESEJAHTERAAN EMOSIONAL SISWA DALAM MATEMATIKA: SEBUAH SYSTEMATIC LITERATURE REVIEW - Andriani, Amelia; Nurhayati, Nurhayati; Ramadani, Gita; Meckial, Zaskia Sri; Gusteti, Meria Ultra; Wulandari, Suci (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The development of digital technology in mathematics education has encouraged a shift in learning from a purely cognitive emphasis to an approach that also considers students' emotional well-being. The mindful learning approach emphasizes awareness of the learning process, self-regulation, positive emotional engagement, and meaningful learning experiences. This article aims to systematically review the results of research on the use of digital platforms and applications in supporting mindful learning and students' emotional well-being in mathematics learning. This study uses a systematic literature review method by analyzing reputable international journal articles published between 2017 and 2025. The results of the study show that the use of digital technology in mathematics learning contributes to increased learning motivation, strengthened self-regulation, reduced mathematics anxiety, and the development of more reflective and meaningful learning experiences. The novelty of this study lies in its integrative synthesis of digital technology, mindful learning, and emotional well-being in the context of mathematics education, which has rarely been discussed comprehensively in systematic literature review studies. These findings emphasize the importance of designing technology-based mathematics learning that consciously integrates the principles of mindful learning to support students' emotional well-being.